1981
DOI: 10.1128/aac.20.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of ampicillin and chloramphenicol for meningeal isolates of group B streptococci

Abstract: The increasing prevalence of ampicillin-resistant Haemophilus influenzae type b has led to the recomxniendation that ampicillin and chloramphenicol be given as the initial therapy for suspected bacterial meningitis in infants and children. However, during the first 2 months of life, H. influenzae type b is a rare cause of meningitis, whereas group B streptococcus is the most frequently isolated agent. Since ampicillin and chloramphenicol have been shown to be antagonistic for other streptococci, an in vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The penicillin MICs obtained in this study agree with those reported by Baker et al (2) Penicillin tolerance has been described in 4% of strains of group B streptococci (15). Tolerant strains had MICs of penicillin that were similar to those of nontolerant strains (mean MIC, 0.04 ,ug/ml), but MBCs of penicillin G were 0.3 to 1.25 pg/ml (mean, 0.6 ,ug/ml) for tolerant strains as compared with 0.04 to 0.3 ,ug/ml (mean, 0.08 jig/ml) for nontolerant strains (8).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The penicillin MICs obtained in this study agree with those reported by Baker et al (2) Penicillin tolerance has been described in 4% of strains of group B streptococci (15). Tolerant strains had MICs of penicillin that were similar to those of nontolerant strains (mean MIC, 0.04 ,ug/ml), but MBCs of penicillin G were 0.3 to 1.25 pg/ml (mean, 0.6 ,ug/ml) for tolerant strains as compared with 0.04 to 0.3 ,ug/ml (mean, 0.08 jig/ml) for nontolerant strains (8).…”
supporting
confidence: 82%
“…Despite the availability of new and effective antimicrobial agents for the treatment of lifethreatening bacterial infections, neonatal meningitis continues to be associated with an unacceptable mortality and morbidity rate (11 (15). Penicillin-treated group B streptococci, however, show increased susceptibility to the bactericidal activity of human polymorphonuclear leukocytes (5).…”
mentioning
confidence: 99%
“…The activity of combinations of penicillin and chloramphenicol is a subject of considerable debate. In vitro, such combinations have been shown to be antagonistic, indifferent, or synergistic against several gram-negative and gram-positive organisms (6,12,14,20,26,30). The in vivo effects of such combinations in experimental infections have been related to drug administration: antagonism occurred when chloramphenicol was given before but not after penicillin administration (15,29).…”
Section: Resultsmentioning
confidence: 99%
“…Chloramphenicol is potentially toxic and produces unpredictable blood levels (13,14), and chloramphenicolresistant isolates of H. influenzae are now recognized. In addition, the combination of ampicillin and chloramphenicol may be antagonistic against some enteric gram-negative rods and group B streptococci, both of which are major pathogens in neonatal meningitis (2,18).…”
mentioning
confidence: 99%